"More bang for the buck": exploring optimal approaches for guideline implementation through interviews with international developers - Gagliardi Anna R (BMC, 2012)
Abstract Background Population based studies show that guidelines are underused. Surveys of international guideline developers found that many do not implement their guidelines. The purpose of this research was to interview guideline developers about implementation approaches and resources. Methods Semi-structured telephone interviews were conducted with representatives of guideline development agencies identified in the National Guideline Clearinghouse and sampled by country, type of developer, and guideline clinical indication. Participants were asked to comment on the benefits and resource implications of three approaches for guideline implementation that varied by responsibility: developers, intermediaries, or users. Results Thirty individuals from seven countries were interviewed, representing government (n = 12) and professional (n = 18) organizations that produced guidelines for a variety of clinical indications. Organizations with an implementation mandate featured widely inconsistent funding and staffing models, variable approaches for choosing promotional strategies, and an array of dissemination activities. When asked to choose a preferred approach, most participants selected the option of including information within guidelines that would help users to implement them. Given variable mandate and resources for implementation, it was considered the most feasible approach, and therefore most likely to have impact due to potentially broad use. Conclusions While implementation approaches and strategies need not be standardized across organizations, the findings may be used by health care policy makers and managers, and guideline developers to generate strategic and operational plans that optimize implementation capacity. Further research is needed to examine how to optimize implementation capacity by guideline developers, intermediaries and users.